Financing the Green Transition: How International Investments Support Renewable Energy Development in Azerbaijan - Mammadzada, Suad; Akbarova, Gular (The Journal of Accounting and Management, 2025)
This paper examines how international investments are driving Azerbaijan’s renewable energy transition, a critical step in reducing dependence on hydrocarbons and aligning with COP29 climate commitments. Most research on Azerbaijan emphasizes hydrocarbons, energy security, and gas exports, while little focuses on renewable finance. Global studies highlight green bonds, blended finance, and regulatory reforms, but their application in hydrocarbon-dependent economies remains underexplored. Using descriptive statistical analysis and a simple econometric projection, the study introduces a Renewable Energy Investment Ratio (REIR) to evaluate the share of renewable finance in GDP. It further analyzes financing structures of flagship projects backed by international financial institutions and private investors. From 2020–2024, renewable investments rose from zero to over USD 600 million, supported by projects such as the Garadagh Solar Plant and Khizi–Absheron Wind Plant. The REIR increased from 0.12% to 0.76%. Projections indicate renewable investments could surpass USD 2 billion by 2030. International financing, coupled with credible regulatory reforms, is vital for scaling Azerbaijan’s renewable energy sector and strengthening energy security.